Do Anti-immigration Attitudes Discourage Immigration? Evidence from a New Instrument - Etienne Bacher; Michel Beine; Hillel Rapoport (CESifo GmbH, 2025)
We investigate the effect of anti-immigration attitudes on immigration plans to Europe. We propose a new instrument for attitudes toward immigration, namely, the number of country nationals killed in terrorist attacks taking place outside of Europe. Our first-stage results confirm that such terrorist attacks increase negative attitudes to immigration in the origin country of the victims. Our second-stage results then show that this higher hostility toward migrants decreases the attractiveness of the country for prospective immigrants at all skill levels.
Keywords: C1; F2; J1; 330; immigration; terrorism; anti-immigration attitudes